(untitled) (Praxis Educativa, 2026)
Education for a digitalised culture is a challenge that calls for the design of various strategies, such as teacher training. The aims of this paper are to characterize the fields of knowledge necessary for training oriented towards the pedagogical inclusion of digital technologies in education and to design an appropriate training model. As a qualitative research, this study has a double character: its analytical-interpretative cut involved the review of recent documents in the main related fields of knowledge; its propositional cut aimed to design a holistic teacher education model. As a result, three complementary and interdependent fields of knowledge were identified and analyzed: Digital Literacy; Media and Information Literacy; Digital Citizenship. Then, a Comprehensive Digital Teacher Education model was then designed that recovers those three fields of knowledge and adds a fourth referring to digitalized subjectivation. These results show the need for training strategies that respond to current educational demands.